2015
DOI: 10.3923/ja.2015.102.111
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Induced Phenotypic Diversity in Chickpea Using Physical and Chemical Mutagenesis

Abstract: A B S T R A C TIn the present scenario of variable natural environment and sky-high population, sustainable boost in the agricultural productivity is the utmost priority. Induce mutagenesis generates noble genetic combination without affecting the overall genomic makeup of crop, thus, providing essential genetic variation for any crop improvement programme. The present study has been carried out to investigate the comparative mutagenicity of gamma rays and HZ on chickpea (Cicer arietinum L.) genotype (avrodhi)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…This assessment also assists to understand the mean deviation induced in the agronomic traits. In chickpea, several morphological mutants based on growth habit, size, leaf, flower and seeds were reported [4,9,[14][15][16][17] with the application of single and combination treatments of physical and chemical mutagens. Since, every individual gene responsible for trait of agronomic interest can mutate, therefore, a wide spectrum of viable morphological mutants can be expected in mutation experiments [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assessment also assists to understand the mean deviation induced in the agronomic traits. In chickpea, several morphological mutants based on growth habit, size, leaf, flower and seeds were reported [4,9,[14][15][16][17] with the application of single and combination treatments of physical and chemical mutagens. Since, every individual gene responsible for trait of agronomic interest can mutate, therefore, a wide spectrum of viable morphological mutants can be expected in mutation experiments [18].…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of economic traits and quality characters for improvement of crop within the short period of time can be achieved by the help of induced mutagenesis [5,6]. Induced morphological mutants are useful for the development of improved varieties when they are used in cross breeding programmes [4,7,8]. Chickpea (Cicer arietinum L.) is an important nutritional pulse crop.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] reported that the lentil germplasm from India exhibits least genetic variability among lentil-producing countries. The adaptation to various stresses through natural selection for high productivity, seed quality, pest and disease resistance and inefficiency of conventional breeding methods exhausted the genetic variability of grain legumes[ 8 ]over the course of time, which resulted in limited accessible genetic variability and hence supplemented breeding strategies needs to be incorporated to serve the objective of crop improvement[ 9 ].Induced mutations technology, over the past decades, appeared to be one of the most coherent approaches for broadening the genetic base in lentil to circumvent the bottleneck conditions. Also, it is highly recommended especially in lentil due to its tiny flower size which makes recombination breeding a very tedious job.…”
Section: Introductionmentioning
confidence: 99%
“…In chickpea, the effectiveness and efficiency of EMS were seven and two times higher than that of γ rays [ 53 ]. In another study, effectiveness of hydrazine hydrates (HZ) towards inducing mutations in quantitative traits was higher than by the γ rays but less than the EMS [ 54 ]. However, in another study, similar effectiveness by exposing with of both the mutagens were found on Stevia rebaudiana [ 55 ].…”
Section: Discussionmentioning
confidence: 99%